Differences in symptoms, first medical contact and pre-hospital delay times between patients with ST- and non-ST-elevation myocardial infarction. Issue 3 (April 2019) - Ängerud, Karin H; Sederholm Lawesson, Sofia; Isaksson, Rose-Marie; Thylén, Ingela; Swahn, Eva
Aim: In ST-elevation myocardial infarction, time to reperfusion is crucial for the prognosis. Symptom presentation in myocardial infarction influences pre-hospital delay times but studies about differences in symptoms between patients with ST-elevation myocardial infarction and non-ST-elevation myocardial infarction are sparse and inconclusive. The aim was to compare symptoms, first medical contact and pre-hospital delay times in patients with ST-elevation myocardial infarction and non-ST-elevation myocardial infarction. Methods and results: This multicentre, observational study included 694 myocardial infarction patients from five hospitals. The patients filled in a questionnaire about their pre-hospital experiences within 24 h of hospital admittance. Chest pain was the most common symptom in ST-elevation myocardial infarction and non-ST-elevation myocardial infarction (88.7 vs 87.0%, p =0.56). Patients with cold sweat (odds ratio 3.61, 95% confidence interval 2.29–5.70), jaw pain (odds ratio 2.41, 95% confidence interval 1.04–5.58), and nausea (odds ratio 1.70, 95% confidence interval 1.01–2.87) were more likely to present with ST-elevation myocardial infarction, whereas the opposite was true for symptoms that come and go (odds ratio 0.58, 95% confidence interval 0.38-0.90) or anxiety (odds ratio 0.52, 95% confidence interval 0.29–0.92). Use of emergency medical services was higher among patients admitted with ST-elevation myocardial infarction. The pre-hospital delay time from symptom onset to first medical contact was significantly longer in non-ST-elevation myocardial infarction (2:05 h vs 1:10 h, p =0.001). Conclusion: Patients with ST-elevation myocardial infarction differed from those with non-ST-elevation myocardial infarction regarding symptom presentation, ambulance utilisation and pre-hospital delay times. This knowledge is important to be aware of for all healthcare personnel and the general public especially in order to recognise symptoms suggestive of ST-elevation myocardial infarction and when to decide if there is a need for an ambulance.